Analysis Of The Influence Of Brand Community Identification, Rewards And Brand Involvement On Brand Loyalty Among Vespa Motorcycle Users In Yogyakarta - Rakha Binuka Belva Taqi Bestari; Agus Abdurrahman (International Journal of Business and Quality Research, 2023)
This research aims to determine the relationship research and the influence of brand community identification, appreciation and brand involvement on brand loyalty among Vespa users in Yogyakarta. The data that will be presented in this research was obtained from the results of distributing questionnaires from 160 samples. Meanwhile, the data collection technique used in this research is non-probability sampling with a purposive sampling method. This research uses purposive sampling because special criteria are needed for the sample to be taken so that it can answer research problems and also provide representative values. Hypothesis testing in this research uses Structural Equation Modeling (SEM) analysis with the help of AMOS 24 software. The results of this research show that there is an influence between the variables of brand community identification, appreciation, brand involvement and brand loyalty.